Erector spinae plane block for pain management after total hip arthroplasty. A systematic review and meta-analysis - Tomasz Reysner; Grzegorz Kowalski; Małgorzata Reysner; Alicja Geisler-Wojciechowska; Monika Grochowicka; Katarzyna Wieczorowska-Tobis (Chirurgia Narządów Ruchu i Ortopedia Polska)
Purpose. The Erector Spinae Plane Block (ESPB) is a widely used regional anesthesia technique in breast, thoracic, and spine surgery. However, its effectiveness and pain-relief capabilities in total hip arthroplasty have not been definitively established. This meta-analysis seeks to establish the analgesic effectiveness of ESPB in total hip arthroplasty.Methods. As per PRISMA guidelines, we carried out a meta-analysis of prospective randomized clinical trials that compared the effects of ESPB in the control group and different peripheral nerve blocks in total hip arthroplasty. The study was registered in the International Register of Systematic Reviews (PROSPERO) and can be accessed online (www.crd.york.uk/prospero, CRD42024498350).Results. Six studies involving 299 participants were critically evaluated and included for analysis. The results showed that ultrasound-guided ESPB led to a decrease in postoperative opioid consumption 24 hours after surgery compared to a placebo (mean difference –4.29, 95% CI –5.33 to –3.25; p < 0.00001). However, there were no significant differences in postoperative pain scores at Department of Palliative Medicine, Poznan University of MedicalSciences, Poznań, Poland 3-6 hours and 24 hours between the two groups.Conclusion. ESPB improved the effectiveness of pain relief in total hip arthroplasty, particularly without nerve block analgesia. More high-quality, well-defined RCTs are urgently required to assess the pros and cons of ESPB for total hip arthroplasty.